Improving the mobile structure of a vertical modular solar dryer for the agricultural sector "From field to fork" - Zahorulko, Andrii; Voronenko, Iryna; Minenko, Sofiia; Pugach, Andrii; Nazarenko, Olena; Lebedenko, Olesya; Ibaiev, Eldar; Tytarenko, Nataliia (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the radiation drying of local agricultural raw materials (Jerusalem artichoke of the "Kyivskyi bily" variety and apples of the "Williams" variety) in a mobile structure of a vertical-modular solar dryer. The study is aimed at improving the resource-saving drying of agricultural raw materials. The solar dryer has adjustable hemispherical air collectors (tilt angle 20…45°) and a heat-insulated chamber with a thermal accumulator (stone pebbles, size 50–80 mm), a backup infrared heater (600 W), and autonomous fans in a combination with Peltier elements. Drying of agricultural raw materials with a thickness of 4–12 mm and a heat carrier speed of 0.05–2.0 m/s was carried out in the summer-autumn decades of 2024. The drying duration of Jerusalem artichoke was 38.6–50 h, apples – 30.5…37 h; drying temperature – 22…50 °C. Moisture removal was 77.8 % for Jerusalem artichoke and 87.0 % for apples. Moisture removal when loading 6.0 kg of raw materials was 3.5 kg for Jerusalem artichoke (77.8 % moisture) and 4.2 kg for apples (87.0 % moisture) under drying conditions to a moisture content of 20.0 %. Losses of vitamin C during sun drying in Jerusalem artichoke were 2.17 times (versus 3.21 times during convective drying), and in apples – 2.26 times (versus 2.58 times). Dietary fiber in Jerusalem artichoke decreased by 2.29 times (versus 3.33 times), and in apples – by 2.25 times (versus 3.91 times). Losses of β-carotene in Jerusalem artichoke during sun drying were 2.65 times (versus 3.08 times). There was also a smaller decrease in phosphorus and mono- and disaccharides. Dried semi-finished products had a uniform appearance, light yellow color, and natural taste and aroma properties. An improved mechanism for managing the competitiveness of agricultural enterprises combines technical, economic, and organizational aspects for entering the European market and expanding exports